PREVENTION OF THROMBOEMBOLIC COMPLICATIONS IN ATRIAL FIBRILLATION - RAT POISON OR NEW ORAL ANTICOAGULANTS: DO WE HAVE A CHOICE, AND SHOULD WE BE AFRAID TO MAKE IT? FIRST CLINICAL EXPERIENCE WITH RIVAROXABAN IN NIZHNY NOVGOROD - L. Y. Koroleva; I. V. Kolesnichenko; V. P. Nosov; I. I. Gritsenko; E. S. Timoschenko (Рациональная фармакотерапия в кардиологии, 2015)
Adequate primary and secondary prevention of thromboembolic complications is one of the main goals of management of patients with atrial fibrillation. Many years of practice and experience of warfarin use, unfortunately, did not lead to wider and more efficient use of anticoagulation therapy. New oral anticoagulants devoid of drawbacks of warfarin, which prevented its prescription and long-term use, have appeared in the past few years. One of them, the most studied, with the largest list of indications for use, and very attractive, is rivaroxaban.